Improving Students’ Pronunciation Ability through Homophone and Rhyming Games - Gabriella Efinda Ratriningtyas; Sri Handayani (Journal of English Language and Education, 2026)
This study focuses on the application of homophone and rhyming games as teaching media to improve students’ pronunciation ability at the tenth grade of SMA N 1 Colomadu in the academic year of 2025/2026 and investigates whether using homophone and rhyming games can improve students’ pronunciation ability at the tenth grade of SMA N 1 Colomadu in 2025/2026 academic year. This research applied Classroom Action Research design. This research was conducted in two cycles started from July to August in the academic year of 2025/2026. This research was gathered using qualitative and quantitative methods. Qualitative data was collected through observation, questionnaire, and documentation. The data was analyzed using Miles and Huberman method. Quantitative data was collected through pre-test, post-test 1, and post-test 2. The data was collected by analyzing the mean score of the tests. The result of the research appeared that the application of homophone and rhyming games proved that the improvement of students’ pronunciation ability. The mean score increased from 65 in the pre-test, 70 in the post-test 1, and 80 in the post-test 2. The application of homophone and rhyming games successfully affected the students at the tenth grade of SMA N 1 Colomadu. The students showed enthusiasm and improvement in their pronunciation performance during teaching-learning process.